Hryhorii Skovoroda's Aphoristics: Structural, Semantic and Stylistic Aspects - Yuliya Kalashnyk (Вісник Харківського національного університету імені В. Н. Каразіна. Серія Філологія. Vìsnik Harkìvsʹkogo nacìonalʹnogo unìversitetu ìmenì V.N. Karazìna. Serìâ Fìlologìâ.)
Consideration of the aphorism of the famous thinker in terms of syntactic construction of the expressed thought and creation of various stylistic techniques in this plane to enhance it is relevant.